To invent yourself: the academic memorial at the crossroads of autobiography and egodocument - Lima Silva, Wilton Carlos [UNESP] (Univ Caxias Sul, Centro Ciencias Humanas, 2016)
Academic memorials are documents produced to meet institutional requirements of progression in the teaching career, with the author describing his history, with an emphasis on researchs, publications in indexed journals, activities in postgraduate courses, lectures and production of qualified materials, extension courses and other activities related to their area of expertise. In addition to the candidate's academic merit assessment tool it is also presented as one of the rare moments in which it is legitimate for the intellectual to speak about himself, addressing options, practices, experiences and memories, as experience. Thus, we understand the academic memorial as a form of autobiographical writing that is conditioned by an intellectual and institutional tradition, in which different levels of subjectivity claim a persona, defined, among other things, by the prominence of narrative models that determine presence and absence in the author's report.
Keywords: Academic memorial; Autobiography; Egodocument; Memory